EFEITOS DO TREINAMENTO DE FORÇA DE BAIXA INTENSIDADE COM RESTRIÇÃO DE FLUXO SANGUÍNEO SOBRE RESPOSTAS AUTONÔMICAS E CARDIOVASCULARES EM IDOSAS HIPERTENSAS. - PINTO, Leandro Moraes (2018)
Purpose: To evaluate the effects of low-intensity strength training with restriction of blood flow on autonomic and cardiovascular responses in hypertensive elderly women. Materials and Methods: This was an experimental, randomized, controlled study with 37 elderly women (63.86 ± 4.65 years) who underwent low intensity strength training (20% of 1 RM), divided into 3 experimental groups: 60% blood flow restriction (RFS) (RF60: n = 12) of the total occlusion pressure (PTO), 80% blood flow restriction (RF80: n = 13) of the PTO and the placebo control group : n = 12) who trained with restriction of blood flow with no pressure. All participants performed 3 sets of 15 repetitions with a 60-second interval between sets. Alternate segment methodology was used in elbow extension, knee extension, elbow flexion and leg press exercises, with frequency of twice a week for eight weeks. The autonomic nervous system was evaluated by the heart rate variability method. Hemodynamic responses by ambulatory blood pressure monitoring (ABPM) and endothelial function by flow-mediated dilatation (DILA) at the beginning and end of the study. Results: The main results found in the RF60 group were the reduction of sympathetic activity and increased cardiac parasympathetic activity, with improvement of baroreflex sensitivity, cardiac sympathovagal balance, reduction of peripheral vascular resistance due to improved endothelial function, with greater arterial dilation and reduction of systolic blood pressure as the final product. In this same group, there was also a reduction in both the double product and the pulse pressure, indicating that there was a positive adaptation with reduction in cardiac effort and improvement in arterial stiffness. While GCP groups and those who trained 80% of RFS did not obtain the same responses in the analyzed variables. Discussion: Studies have shown acute hypotensive effects in low intensity strength training sessions with restriction of blood flow in healthy elderly women and those affected by systemic arterial hypertension (SAH), being more efficient in reducing blood pressure in hypertensive patients compared to training of strength with moderate and high intensities, to prevent the Valsalva maneuver and to provide less perceived exertion, in addition, several authors suggest that this type of training seems to be safe in the cardiovascular sphere. Conclusion: Low-intensity strength training with restricted blood flow, when performed at moderate restriction intensity (60% of the PTO), was able to provide benefits in the autonomic and cardiovascular system in the elderly, being, therefore, the intensity of RFS to obtain such benefits for the population in question.